The Charlie method - Kennedy, Elle (Kennedy, Elle. Campus diaries, 2025)
"College senior Charlotte Kingston is living two lives--and she's nailing both of them. By day, she's the perfect soroity girl, a STEM student in biomedical engineering, and the adopted daughter of an overachiever family. At night, she's Charlie: a risk-taking daredevil looking for fun who finds herself chatting on a dating app with two anonymous hotties. Will Larsen may seem like the breezy boy next door, but his Congressman father is a constant thorn in his side. After a scandal hits another Division 1 hockey program, Will's dad is determined to distance his son from it, hiring a journalist toprove how squeaky-clean Will and his team are. Which means the lastthing Will wants is for anyone to find out he and his best friend Beckett Dunne ... sometimes share girls in the bedroom. When Charliefinally meets them in person and realizes she's been chatting with two gorgeous Briar U hockey players, things get steamy--fast. But all their messy secrets are piling up, and real life soon threatens toshatter the fantasy"--